What do we mean by a level playing field in international aviation? - Mike Tretheway; Robert Andriulaitis (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2015)
The concern about a level playing field has raised its profile in aviation in recent years, yet few have defined what constitutes a level playing field, or alternatively, what makes a playing field unlevel. In this paper we review elements that are often cited in arguments about whether access should or should not be granted, and on what terms. We find the following do not constitute legitimate factors that should be addressed in an air services agreement in order to make a playing field "level: Geographic advantage/disadvantage; Size of carrier; Differences in the cost of factors of production; 6th freedom traffic opportunities; Technological advantage; and Airport slots. Legitimate areas of concern include safety and general carrier-specific subsidies. The latter concern does not include transparent subsidies for specific air service obligations, especially if eligibility for such subsidy is competitive and non-discriminatory. It also does not exclude economically efficient subsidies to infrastructure. There is a need to keep watch on developments in global alliances, or potential cross-border mergers and acquisitions, to ensure the resulting carrier combinations do not engage in activities that constitute an abuse of market power. The mechanism to deal with this, however, is through the application of competition law. It should not be addressed by bilateral air service agreements. Many of the complaints heard today are attempts to negate natural inherent competitive advantages. This effectively seeks to deny consumers the benefits of lower costs and/or better service that arise from geographic, management and other legitimate advantages inherent to a number of air carriers.
Keywords: 330; Luftverkehr; Internationaler Wettbewerb; Luftrecht